Analisis Pengaruh Variasi Komposisi terhadap Kekuatan Tarik Komposit Serat Sabut Kelapa - Zidane Al Bayan Sulaksono; Fais Hamzah; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
One of the transportation supporting the economy in Indonesia is the ship. The government prioritizes the maritime sector in national development, which has a positive impact on the domestic shipping industry in the production of ships with various raw materials being developed. Fiberglass is a type of FRP (Fiber Reinforced Plastic) reinforcing fiber. In the manufacture of FRB (Fiber Reinforced Boat), fiberglass is an important part, its texture is light, and sharp, easily blown by the wind and can be inhaled into the breath which is not good for health. Indonesia is overgrown with coconut plants, parts of the coconut plant have many benefits, but coconut coir is less used, and is considered a waste that accumulates under coconut plants and is left to rot, therefore it is necessary to use coconut coir as an alternative to natural fiber from coconut coir. Synthetic fibers in the manufacture of composites. In this study, a study was conducted on the effect of composition on the tensile strength of coconut fiber reinforced composites, using a fiber delignification time of 45 minutes and the variation of fiber composition was 20%, 30% and 40% based on volume fraction. Coconut coir fiber is carried out by delignification process using NaOH solution with a concentration of 5% for 45 minutes. The composite with the highest tensile strength was 40% fiber composition, which was 60.96 ± 6.36 MPa. While the lowest tensile strength with a fiber composition of 20% is 31.88 ± 9.51 MPa.